Optimisation‐based collaborative determination of component trustworthiness in service compositions. Issue 6 (17th March 2014) - Elshaafi, Hisain; Botvich, Dmitri
Abstract: In service‐oriented environments, service providers orchestrate distributed services from other providers to create new composite enterprise services. A component service can be invoked jointly by several distributed composite service providers. However, because a composite service is provided to the consumers as an integrated service, when failures or dissatisfaction of the consumers occurs, it is not possible to directly identify the untrustworthy component. In this paper, we describe a collaborative trustworthiness determination approach using optimisation that can provide a solution to selecting trustworthy component service constructs based on monitoring and consumer quality of experience reporting of existing composite services from peer providers. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : The paper describes an optimisation‐based approach for the determination of component service trustworthiness based on the trustworthiness attributes of collaborating composite services. The approach can identify untrustworthy components and detect the trustworthiness of candidate components to be selected for new compositions. The composite services jointly invoke distributed component services. The paper covers some of the important attributes of trustworthy services that are service reliability, reputation and response time.